Design and preliminary performance tests of the TFMTF-LIPAc Cryoplant. (April 2019) - Renard, B.; Machefel, A.; Maebara, S.; Phillips, G.; Pruneri, G.; Brédy, Ph.; Riquelme, A.; Vincent, B.; Legrand, J.; Gire, C.; Ebisawa, T.; Wanner, M.
Abstract: Special features of this Cryoplant are first given with operating purpose, main constraints, design choices for this cryoplant which will cool down a superconductive module (SRF Linac) of an accelerator currently under installation in Japan. The relationship between compliance with Japanese regulations and the successful hydraulic, electric and instrumentation tests are discussed. Measurements of refrigeration power and liquefaction rate were achieved inside the Dewar, and margin power was measured. Further functional and performance tests were conducted in order to demonstrate the correct operation of the cryogenic lines and distribution systems. These tests were performed successfully without the cryomodule, in anticipation to its installation and operation.